Undergraduate Students' Understanding of Physiology Subject, Opinions and Perception: The Case of Bayero University, Kano, Nigeria (Nigerian Journal of Physiological Sciences, 2021)
Summary: Human Physiology courses are compulsory in medical education but many students encounter challenges in studying them. This study investigates understandings, opinions and perceptions of students about physiology subject and the challenges they encounter in their study. Two hundred and eighty (280) students were interviewed using structured questionnaire. The data were analyzed using IBM SPSS statistics 22. The mean age of the students was 22.8 ± 4.1 years. Males constituted 174(62.1%), while females were 106 (37.9%). Majority of the respondents were in 300 level of study in the university 178(63.6%) as of the time of conducting this research. Most of the participants 257(91.8%) claimed to have good to excellent understanding of the physiology subjects. One hundred and nine (39.1%) alleged that academic staff had unfriendly attitude like rushing lectures, commencing lectures late and fixing tests and other continuous assessment close to examinations, and that lecturers have poor communication/ teaching skills. Less than one-third (28.7%) believed that the subjects have bulky course contents, and 56(20.1%) were of the opinion that the students' lack of seriousness or interest is among the reasons for failing physiology courses. On binary logistic regression, being of female sex, and in 300 level of study emerged as the independent predictors of the students' perception of physiology. Improving the pedagogy 102(36.4%), good attitude of staff towards students and teaching 73(26.1%), improving infrastructure and equipment 35(12.5%); and instituting guidance and counseling unit for both staff and student 31(11.1%) were the ways suggested by the students for improving performance in physiology subject. Most of the students had poor and negative perception about physiology subjects (83.2%). Guidance and counseling for students, through the level coordinators and the mentor-mentee program should be strengthened in all departments. Basic infrastructure and equipment, and teaching techniques should also be upgraded.